From LiB3O5 to NaRbB6O9F2: Fluorine‐Directed Evolution of Structural Chemistry. Issue 40 (27th June 2018) - Han, Shujuan; Zhang, Bingbing; Yang, Zhihua; Pan, Shilie
Abstract: Introducing fluorine into borates indicates the direction for structural evolution. A new fluorooxoborate, NaRbB6 O9 F2 featuring a unique [B6 O9 F2 ]∞ layered structure and excellent optical properties has been synthesized. It is further demonstrated that incorporation of fluorine can enrich the structural chemistry of borates. Abstract : Structural evolution : NaRbB6 O9 F2, a new fluorooxoborate features a unique [B6 O9 F2 ]∞ layered structure consisting of BO3, BO4 and BO2 F2 polyhedra, which represents a new structure type of fluorooxoborate.